Intercultural Communicative Competence in Maritime English: A Mixed-Methods Study of Indonesian Cadets Using Simulation-Based Training - Agus Sulistiono; Rudi Hartono; Nyayu Yayu Suryani; Mahsunah Etik Rahayuningsih (International Journal Labs, 2025)
Intercultural communication has become a central component of Maritime English (ME) due to the increasing multicultural composition of ship crews and the safety-critical nature of communication at sea. While the Standard Marine Communication Phrases (SMCP) provide a foundational linguistic framework, effective shipboard interaction requires broader intercultural communicative competence (ICC), including pragmatic adaptation, negotiation strategies, and the ability to interpret diverse accents and hierarchical norms. Existing literature notes limitations in traditional ME instruction, particularly in seafarer-supplying nations such as Indonesia, where teaching remains focused on grammar and phrase memorization with limited exposure to authentic intercultural interactions. This study investigates the ICC of Indonesian cadets through a convergent mixed-methods design integrating an adapted Intercultural Sensitivity Scale, simulation-based communicative tasks, and semi-structured interviews. A total of 120 cadets participated in routine and emergency maritime simulations designed to elicit pragmatic strategies, clarity, and communication repair behaviours. Quantitative findings reveal significant post-simulation improvements in interaction confidence, attentiveness, and engagement. Qualitative analysis further identifies recurring challenges in pragmatic appropriateness, accent intelligibility, and communication anxiety, yet demonstrates the role of simulation-enhanced training in fostering communicative adaptability and reducing hesitation in multicultural scenarios. The study contributes empirical evidence on ICC development in maritime education and highlights the need to integrate intercultural and simulation-based pedagogy into Maritime English curricula. Recommendations are offered for curriculum designers, instructors, and policymakers to strengthen cadets’ readiness for multinational shipboard environments and align training with contemporary safety and communication demands in global shipping.